Rondoniense flora species potentially active to control parasites in Colossoma macropomum Cuvier (2022)
Considering the economic importance of the fish sector in Rondônia (in the Western Brazilian Amazon), which has been facing losses due to parasites in production systems, the present study aimed to carry out a survey of genetic resources of the flora of Rondônia, with potential properties to control parasites in Tambaqui, the main native species cultivated in the State. Therefore, based on a semi-structured questionnaire, bioprospecting was carried out in 20 municipalities, which are the largest producers at State level. The collected botanical materials were processed according to conventional herborization techniques and taxonomically determined. A total of 54 plants from the flora of Rondônia (38 determined at the species level, 16 at the genus level), distributed in 49 genera and 30 botanical families, have alleged antiparasitic properties for use in fisheries.